Association of Lipid Profile, high-Sensitivity Cardiac Troponin and Haemoglobin A1c in Diabetic Patients with and without ischemic heart disease - Ammer Muheisen Alsaeedy; Alaa S. Alattab; Dhamiaa Maki Hamza; Ahmed Hussein Al Myali (Karbala Journal of Medicine, 2025)
Background: Type 2 diabetes mellitus (T2DM) increases oxidative stress, with dyslipidemia, specifically uncontrolled T2DM, along with increased body mass index (BMI), all these factors increasing the risk of cardiovascular disease. The interplay between lipid profile, high-sensitivity cardiac troponin I (hs-cTnI), Hemoglobin A1c (HbA1c), and BMI in diabetic patients with is-chemic heart disease IHD remains critical for risk stratification and management. The study aimed measurement of lipid profile, hs-cTnI, HbA1c levels, and BMI as predictive biomarkers for ischemic heart disease in diabetic patients. Methods: This case-control study was conducted at the Department of Microbiology, College of Medicine at the University of Kerbala in collaboration with the Cardiology Unit at Karbala Teaching Hospital. A total of 180 individuals aged 35–65 years were enrolled, including 120 patients with T2DM (60 with myocardial ischemia and 60 without) and 60 age- and sex-matched healthy controls. Blood samples were collected to measure HbA1c and lipid profile. Results: Patients with T2DM and ischemia showed significantly higher levels of HbA1c, low-density lipoprotein cholesterol (LDL-C), triglycerides, and very low-density lipoprotein cholesterol (VLDL-C), and lower high-density lipoprotein cholesterol (HDL-C) than non-ischemic diabetic patients and controls (p < 0.05). HbA1c positively correlated with lipid abnormalities. There are no significant differences in hs-cTnI levels between diabetic patients without ischemia com-pared to controls Conclusions: Elevated HbA1c and lipid derangements are strongly associated with myocardial ischemia in T2DM patients. These biomarkers can serve as early indicators of cardiovascular risk. Tight glycemic and lipid control should be emphasized to prevent ischemic complications in diabetic populations. Keywords: Type 2 diabetes mellitus, Ischemic heart disease, HbA1c, Lipid profile, BMI, hs-cTnI